2007
DOI: 10.1080/87565640701190775
|View full text |Cite
|
Sign up to set email alerts
|

Error-Related Negativity in a Visual Go/No-Go Task: Children vs. Adults

Abstract: Thirteen young adults (ages 21-25) and nine children (ages 7-11) were tested on a visual go/no-go task comparing response times (RTs), error rates, and amplitude and latency changes of error-related negativity (ERN). All experimental conditions were identical for both age groups. Results are consistent with the previous flanker task research showing an increase in ERN amplitude as children age. However, the present results indicate that the peak amplitude of ERN for 9-11 year old children is larger than that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
33
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 11 publications
8
33
1
Order By: Relevance
“…Finally, the discrepancy between this report and Larson's findings may reflect age-related differences in relative ERN amplitudes. Both women and men in the current study were considerably younger than those included in the study by Larson and colleagues. Several studies have noted developmental changes in ERN amplitude (Davies et al, 2004;Kim et al, 2007;Wiersema et al, 2007;Ladouceur et al, 2004). Thus, this may represent sexual dimorphism in the development of performance-monitoring processes.…”
Section: Discussionmentioning
confidence: 93%
“…Finally, the discrepancy between this report and Larson's findings may reflect age-related differences in relative ERN amplitudes. Both women and men in the current study were considerably younger than those included in the study by Larson and colleagues. Several studies have noted developmental changes in ERN amplitude (Davies et al, 2004;Kim et al, 2007;Wiersema et al, 2007;Ladouceur et al, 2004). Thus, this may represent sexual dimorphism in the development of performance-monitoring processes.…”
Section: Discussionmentioning
confidence: 93%
“…Brain event-related potential (ERP) studies have identified the ERN as a robust marker of anterior cingulate cortex-mediated cognitive control processes invoked by performance errors (Holroyd & Coles, 2002;Yeung, Botvinick, & Cohen, 2004). The ERN is clearly evident in adolescents as well as adults (Davies, Segalowitz, & Gavin, 2004) and, more recently, has been observed in young children (i.e., ages 5-11; Kim, Iwaki, Imashioya, Uno, & Fujita, 2007;Torpey, Hajcak, Kim, Kujawa, & Klein, 2012;Wiersema, van der Meere, & Roeyers, 2007). The ERN thus represents a neurophysiological marker of cognitive control across development.…”
Section: Clinical Feasibility Of Measuring Neurobehavioral Constructsmentioning
confidence: 96%
“…These initial studies indicated that clear ERNs were not present in children under 12 years of age, suggesting that mid-to-late adolescence was an important period for the development of this neural response (Davies et al, 2004; Ladouceur et al, 2007; Ladouceur et al, 2004). Subsequent reports indicated that ERN was observable in groups of children ranging in age from 7 −11 (Kim et al, 2007; Wiersema et al, 2007), with non-significant increases in ERN amplitude observed with increasing age. More recent investigations, involving increasingly developmentally sensitive measures, have demonstrated that the ERN can be identified in groups of children as young as 5 and 6 years old (Torpey et al, 2008; Torpey, et al, 2012).…”
Section: 3 Developmental Changes In the Ernmentioning
confidence: 99%